"I Called us the Sacrificial Lambs": Experiences of Nurses Working in Border City Hospitals During the First Wave of the COVID-19 Pandemic. Issue 1 (March 2023) - Ménard, A. Dana; Soucie, Kendall; Freeman, Laurie A.; Ralph, Jody; Chang, Yiu-Yin; Morassutti, Olivia
Background: The first wave of the COVID-19 pandemic had a significant impact on the personal and professional lives of frontline nurses. Purpose: The purpose of this descriptive phenomenological study was to explore the experiences of Canadian Registered Nurses (RNs) working in Ontario or United States hospitals during the first wave of the COVID-19 pandemic. Methods: Semi-structured interviews were conducted with 36 RNs living in Ontario and employed either at an Ontario or United States hospital. Three main themes were identified across both healthcare contexts. Results: 1) The Initial Response to the pandemic included a rapid onset of chaos and confusion, with significant changes in structure and patient care, often exacerbated by hospital management. Ethical concerns arose (e.g., redeployment, allocation of resources) and participants described negative emotional reactions. 2) Nurses described Managing the Pandemic by finding new ways to nurse and enhanced teamwork/camaraderie; they reported both struggle and resiliency while trying to maintain work and home life balance. Community responses were met with both appreciation and stigma. 3) Participants said they were Looking Forward to a "new normal", taking pride in patient improvements, accomplishments, and silver linings, with tempered optimism about the future. Many expressed a reaffirmation of their identities as nurses. Differences between participants working in the US and those working in Ontario were noted in several areas (e.g., initial levels of chaos, ethical concerns, community stigma). Conclusions: The COVID-19 pandemic has been very difficult for nursing as a profession. Close attention to post-pandemic issues is warranted.